Fluctuating Transnationalism : Social Formation and Reproduction among Armenians in Germany - Chaloyan, Astghik (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
This book concerns various modes of being transnational among a diasporic population-Armenians in Germany-by drawing parallels between the first and second generation migrants. It puts forth the questions as to whether or not, and which kind of transactional activity/ties/practices survive over generations, and to what extent transnational engagements influence self-identification and the sense of belonging. It also examines how various modes of transnationalism, in turn, impact the sense of belonging. The book fleshes out new perspectives and interpretations of transnationalism, by revealing specific aspects of border-spanning ties, and by showing that connections to the country of origin do not necessarily need to be sustained or intensive in order to survive. They can, instead, fluctuate depending on various factors but still have the "right" to be called transnational. Contents Transnationalism and diaspora Historical background of Armenian migration, and formation of the Armenian diaspora Peculiarities of Armenian transnational ties Modes of representation in transnational social fields Components of belonging Target Groups Scholars and students of migration, transnationalism and diaspora studies, sociology Diaspora associations, migration officers The Author Astghik Chaloyan is a scientific assistant at Georg-August University of Göttingen, Institute for Sociology, and Max Planck Institute for the Study of Religious and Ethnic Diversity. .
Keywords: Social sciences.; Religion and culture.; Emigration and immigration.; elektronické knihy; electronic books